Future-proofing students in higher education with unmanned aerial vehicles technology: A knowledge management case study - MENKHOFF, Thomas (Institutional Knowledge at Singapore Management University, 2022)
In this paper we report experiences in implementing a new course ‘Understanding Drone & Robotics Technology – History, Usage, Ethics & Legal Issues’ at the Singapore Management University framed as a strategic knowledge management (KM) initiative in an institution of higher learning aimed at capturing, sharing and creating new knowledge about disruptive technologies such as unmanned aerial vehicles. We posit the new course as a knowledge innovation initiative (similar to a KM-enabled business case in a corporate setting) in support of the university’s mission and vision so as to deliver new value to students and to stay ahead of the latest technological developments. In line with a ‘normal’ KM initiative, we examine how the new learning and teaching initiative was conceived, pushed forward and eventually launched, creating a new multi-disciplinary learning experience for students, instructors and other stakeholders. We explain the knowledge strategy of the course and use I. Nonaka’s SECI framework to shed light on selected aspects of the pedagogical approach towards achieving the desired learning outcomes. Overall, the paper intends to make a case for more collaborative knowledge leadership as a strategic enabler of multi-disciplinary knowledge innovation in a rapidly changing higher education landscape.